2021
DOI: 10.3389/fmed.2021.775280
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Implications of Complement Genetic Variants in Kidney Transplantation

Abstract: Genetic testing has uncovered rare variants in complement proteins associated with thrombotic microangiopathy (TMA) and C3 glomerulopathy (C3G). Approximately 50% are classified as variants of uncertain significance (VUS). Clinical risk assessment of patients carrying a VUS remains challenging primarily due to a lack of functional information, especially in the context of multiple confounding factors in the setting of kidney transplantation. Our objective was to evaluate the clinicopathologic significance of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The functional consequences of rare and unique variants observed in CFH were characterised using 293T cells transfected under serum‐free conditions 23 . Functional studies and surface plasmon resonance (SPR) interaction analyses with the Biacore X100 and Biacore 2000 instruments (GE Healthcare) were performed as previously described 22,24 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional consequences of rare and unique variants observed in CFH were characterised using 293T cells transfected under serum‐free conditions 23 . Functional studies and surface plasmon resonance (SPR) interaction analyses with the Biacore X100 and Biacore 2000 instruments (GE Healthcare) were performed as previously described 22,24 .…”
Section: Methodsmentioning
confidence: 99%
“…The functional consequences of rare and unique variants observed in CFH were characterised using 293T cells transfected under serum-free conditions. 23 Functional studies and surface plasmon resonance (SPR) interaction analyses with the Biacore X100 and Biacore 2000 instruments (GE Healthcare) were performed as previously described. 22,24 Variants in CCP19 and CCP20 were purified as described, with the exception that they were eluted from a HisTrap column (GE Healthcare) at 285 mM NaCl as compared with variants in CCP2 and 3, which were eluted at 95 mM.…”
Section: Functional Studiesmentioning
confidence: 99%
“…Recently, Ren et al evaluated the clinicopathologic significance of genetic variants in a TMA and C3G kidney transplant cohort. The group reported 10 variants in CFH , of which were four pathogenic, one was likely benign, and five were classified as variants of uncertain significance (Ren, Perkins, Love‐Gregory, Atkinson, & Java, 2021). The presence of pathogenic variants increased the risk for recurrent disease in the transplant due to continued complement dysregulation in the recipient.…”
Section: Patient Evaluation and Treatmentmentioning
confidence: 99%
“…The majority of patients only carried polymorphisms or risk haplotypes. 16 , 31 Interestingly, we found that the 64% of patients carried the MCP aHUS risk haplotype C.∗897 T>C (rs7144). This condition affects the promoter region of the MCP gene and results in decreased gene transcription, suggesting a decrease expression of MCP on the cell surfaces.…”
Section: Discussionmentioning
confidence: 72%